2013
DOI: 10.1093/eurjhf/hft083
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency is a key determinant of health‐related quality of life in patients with chronic heart failure regardless of anaemia status

Abstract: AimsTo evaluate the effect of iron deficiency (ID) and/or anaemia on health-related quality of life (HRQoL) in patients with chronic heart failure (CHF).Methods and resultsWe undertook a post-hoc analysis of a cohort of CHF patients in a single-centre study evaluating cognitive function. At recruitment, patients provided baseline information and completed the Minnesota Living with Heart Failure questionnaire (MLHFQ) for HRQoL (higher scores reflect worse HRQoL). At the same time, blood samples were taken for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
172
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(187 citation statements)
references
References 25 publications
3
172
1
5
Order By: Relevance
“…Prevalence rates of iron deficiency (ID) in Southeast Asian HF patients also exceed those in European patients, averaging 61% and peaking at 80% in patients of Indian ethnicity 3. Regardless of ethnicity, geographical location, and anaemia status, concurrent HF and ID has consistently been associated with poor outcomes such as reduced exercise capacity, reduced quality of life (QoL), and elevated risks of HF hospitalization and mortality 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates of iron deficiency (ID) in Southeast Asian HF patients also exceed those in European patients, averaging 61% and peaking at 80% in patients of Indian ethnicity 3. Regardless of ethnicity, geographical location, and anaemia status, concurrent HF and ID has consistently been associated with poor outcomes such as reduced exercise capacity, reduced quality of life (QoL), and elevated risks of HF hospitalization and mortality 4, 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%
“…Less obvious interactions are the presumed direct promoting effect of FGF-23 on cardiomyocyte hypertrophy [17] and the anemia-independent worsening effect of iron deficiency on heart function [18]. Our results argue for an association between the bone mineral axis and iron metabolism.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies have demonstrated that patients with HFpEF with iron deficiency suffered from a similar impact on health-related QoL as patients with HFrEF [17, 28]. Moreover, in both HFrEF and HFpEF, concomitant iron deficiency informs for all-cause mortality independent of the presence or absence of anemia [29].…”
Section: Iron In Diastolic Hfmentioning
confidence: 99%